2020
DOI: 10.1093/schbul/sbaa031.296
|View full text |Cite
|
Sign up to set email alerts
|

S230. The Impact of Social Identity on Self-Esteem and Paranoia

Abstract: Background As theorized by Abraham Maslow, a fundamental need of all humans is to seek a sense of belonging through meaningful social relationships. This universal process drives social identification, the incorporation of these important relationships into one’s own identity. Over the past several decades, social identity has been implicated in various studies of mental health for the protective role that it plays (Haslam et al. 2015). Paranoia is a core symptom of the schizotypy spectrum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Empirical evidence supports this idea. For instance, research has shown that self-esteem is significantly predicted by social identity, personal identity, and ethnic or racial identity [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ], and high self-esteem students scored significantly higher on vocational identity [ 62 ]. Nevertheless, how different vocational identity statuses associate with self-esteem remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence supports this idea. For instance, research has shown that self-esteem is significantly predicted by social identity, personal identity, and ethnic or racial identity [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ], and high self-esteem students scored significantly higher on vocational identity [ 62 ]. Nevertheless, how different vocational identity statuses associate with self-esteem remains unanswered.…”
Section: Introductionmentioning
confidence: 99%